2020
DOI: 10.1111/tmi.13394
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and management of non‐obstetric fistula in the Democratic Republic of Congo: experience from the Fistula Care Plus project

Abstract: objective To describe the frequency, causes and post-repair outcomes of NOF in hospitals supported by the Fistula Care Plus (FC+) project in the Democratic Republic of Congo.methods Retrospective cohort study from 1 January 2015 to 31 December 2017 in three FC + supported fistula repair sites.results Of 1984 women treated for female genital fistula between 2015 and 2017 in the three FC + supported hospitals, 384 (19%) were considered to be non-obstetric fistula (NOF) cases. 49.3% were married/in a relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…There is growing concern that cesarean births are the most important cause of iatrogenic fistulas in sub-Saharan Africa [ 4 ]. Reports indicate that between 77 and 80.2% of iatrogenic fistulas follow surgery for obstetric complications, whether cesarean section, uterine rupture repair or hysterectomy [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing concern that cesarean births are the most important cause of iatrogenic fistulas in sub-Saharan Africa [ 4 ]. Reports indicate that between 77 and 80.2% of iatrogenic fistulas follow surgery for obstetric complications, whether cesarean section, uterine rupture repair or hysterectomy [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Niger 9.9% of 624 fistulas were iatrogenic, [ 6 ] while in the D.R. Congo 19.4% of 1984 fistulas were non-obstetric, with iatrogenic fistulas accounting for an unspecified share [ 5 ]. In Ethiopia, a review of 2593 women with fistula found that 24.6% had “high bladder fistula (predominantly after surgery).” [ 7 ] High fistula similarly accounted for 26.3% (119/452) of vesico-vaginal fistulas in Malawi, “likely due to operative injury rather than obstructed labor.” [ 8 ] Among 229 women with fistula following cesarean birth in the D.R.Congo, 24.0% had iatrogenic injuries [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Location and circumstances can indicate that a fistula is iatrogenic rather than attributable to pressure necrosis [ 7 , 11 ]. Evidence has been mounting about the proportion of iatrogenic fistula amongst repaired fistulas [ 18 21 ]. In a separate analysis we reported that 26.8% (787/2,942) of women with fistula after cesarean section have injuries caused by surgery rather than pressure necrosis from prolonged, obstructed labor [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primary infection and malignancy have also been cited as rare causes of RVF. 7 8 Etiologies such as inflammatory bowel disease (IBD) and radiation therapy are common in Western countries, but their prevalence is not well known in LMICs where the diagnosis of IBD is uncommon and access to radiation therapy rare.…”
Section: Prevalence and Etiologymentioning
confidence: 99%
“…Current literature generally does not cite sexual violence as a cause of RVF but documented cases exist in Rwanda, Sierra Leone, Sudan, and the Democratic Republic of Congo. 8 19 One report of 4,715 women who suffered sexual violence in Eastern Congo found 702 (14.9%) patients had a genital fistula. The authors define genital fistula as either VVF or RVF and report that of the 702 women with genital fistula, 26.6% were obstetric and 63.4% were traumatic.…”
Section: Prevalence and Etiologymentioning
confidence: 99%